Digital Pathways to MICE Competitiveness in Bali: Social-Media Affordances, Omnichannel Integration, and Destination Image - Pondang Polikarpus Nainggolan; I Ketut Sutapa; I Nengah Subadra; Luh Komang Candra Dewi (Journal of Applied Sciences in Travel and Hospitality, 2026)
This study investigates how Social-Media Affordance Quality (SMAQ) and Omnichannel Integration Quality (OCIQ) shape Bali’s MICE destination image (DI-MICE) and perceived MICE destination competitiveness (PMDC), and whether these effects differ between first-time and repeat international visitors. Data were collected through purposive intercept surveys at MICE-related hotels, venues, and attractions in Bali, targeting international visitors who had interacted with Bali’s official MICE digital channels. A quantitative cross-sectional design was applied to 300 valid responses and analyzed using PLS-SEM (SmartPLS 4). The results show that SMAQ and OCIQ significantly enhance destination image and perceived competitiveness, with destination image acting as a key mediator. Multi-group analysis reveals that first-time visitors rely more strongly on social-media affordances, whereas repeat visitors respond more to seamless omnichannel integration. Once an image is formed, both groups evaluate competitiveness similarly. These findings position digital affordances and omni-channel integration as strategic signals of professional capability, offering practical guidance for MICE destination managers in Bali and comparable emerging destinations.